The Principles of Natural Justice: A Comparative Analysis between Secular and Islamic Law in Administrative Decision-Making - Abubakar, Yusuf Sani; Aji, Rajali Haji; Saidi, Mpawenimana Abdallah (Universitas Islam Negeri Alauddin Makassar, 2025)
This study aims to examine the principles of natural justice as conceptualized and applied in both common law and Islamic legal systems, with particular attention to the right to a fair hearing (audi alteram partem) and the rule against bias (nemo judex in causa sua). The underlying values, interpretive methods, and procedural expressions of these principles were also assessed across distinct legal traditions. The study procedures were carried out using a qualitative comparative legal methodology. Data were obtained from primary sources, judicial precedents, and scholarly interpretations to analyze the doctrinal foundations and practical applications in both systems. The results showed that although Islamic law was based on religious texts and common law on judicial precedents, both systems upheld the core values of justice, fairness, impartiality, and procedural integrity. Islamic law established these principles in the Qur’an, Sunnah (Hadith), and interpretive tools, such as ijtihād, maṣlaḥah, and istiḥsān, while common law emphasized constitutional norms and case law. The originality of this study lies in its integrated approach, which shows both the convergence and divergence of procedural justice across secular and religious frameworks. The results are significant for fostering cross-cultural legal understanding and informing reforms in pluralistic jurisdictions. Although primarily theoretical, this current study provides a foundation for future empirical studies in countries such as Malaysia, Indonesia, and Nigeria, where both systems co-exist. These further studies could enrich discussions on legal pluralism and support the development of more inclusive legal systems.